AB0406 Clinical Experience from Abatacept Use in Systemic Lupus Erythematosus: Effectiveness and Safety. (15th July 2016) - Serrano-Benavente, B.; Bello, N.; Nieto-González, J.C.; Ovalles-Bonilla, J.G.; Janta, I.; González-Benítez, R.; Mata, C.; Hernández-Flόrez, D.; Lόpez-Longo, F.J.; Naredo, E.; González-Fernández, C.M.; Monteagudo, I.
Abstract : Background: Biologicals therapies have been used for the treatment of Systemic Lupus Erythematosus (SLE) but only Belimumab has been approved by the European Medicines Agency. Abatacept (ABA), a T-cell co-stimulation blocker, has been proposed as an effective treatment for SLE due to its mechanism of action. Three randomised clinical trials have been performed with ABA in patients with SLE. Although any of these trials met the primary outcome of efficacy, it is still considered as an "off-label" option when none of the other conventional therapies have worked. Objectives: To assess effectiveness and safety of ABA in patients diagnosed of SLE in a Rheumatology service from a tertiary care hospital in Madrid, Spain. Methods: We performed an observational retrospective study in patients with SLE (according to the 1997 American College of Rheumatology classification criteria) who received treatment with ABA. We recorded demographic, clinical and laboratory parameters at the beginning of treatment, and after 6 and 12 months of treatment. We also recorded adverse events. Results: We included 8 patients, all of them women. The median age was 45.13 years (range 30–67 years) and the median time from SLE diagnosis to ABA treatment was 12.12 years (range 3–21 years). Three patients had an overlap disease with Rheumatoid Arthritis. The most frequent symptoms were arthritis (n=5), cutaneous (n=3) and neurological symptoms (n=5), specifically organic brain syndrome (n=4) and lupus headache (n=3). None of the patients had renal disease. In all patients ABA was use after anti-TNFα or Rituximab treatment. One patient discontinued ABA after 2 months due to inefficacy, so she was excluded from statistical analysis. Table 1 shows clinical and laboratory parameters at the beginning of treatment and after 6 and 12 months of treatment. After 6 months of treatment, disease activity according to SLEDAI decreased. One patient persisted with organic cerebral syndrome. After 12 months of treatment neurological symptoms showed a substantial improvement in every patient that presented them at the beginning. Four patients showed significant improvement of arthritis. Two patients experienced serious infections that required hospitalization. Conclusions: ABA was effective in our SLE patients. Clinical response was evident at 6 months and persisted at 12 months. ABA may be a therapeutic option in SLE patients with inadequate response to conventional therapies, specially if arthritis or neurological symptoms are present. References: Aringer M. Expert Opin Drug Saf. 2015;14:243–51. Ikeda K. Clin Dev Immunol. 2013;2013:697525. Disclosure of Interest: None declared